Efektivitas Arbitrase dalam Penyelesaian Sengketa Proyek Infrastruktur: (Studi Kasus Bank Garansi Bodong pada Jalan Tol Pandaan-Malang) - Herlambang Herlambang (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The resolution of disputes in infrastructure projects requires an effective mechanism to ensure smooth project implementation. The fraudulent bank guarantee case in the Pandaan-Malang Toll Road project revealed weaknesses in public procurement oversight, where PT Setdco submitted a falsified bank guarantee, potentially causing losses to the Ministry of Public Works (PU) amounting to IDR 26.09 billion. This study aims to evaluate the effectiveness of arbitration as a dispute resolution mechanism in this case. The research employs a descriptive-analytical method with a qualitative approach, utilizing primary data such as arbitration documents and contracts, and secondary data from legal literature and media reports. The findings indicate that arbitration conducted through BANI provided a fast, fair, and binding solution for the disputing parties. However, the effectiveness of arbitration relies on the supervision of award implementation and regulations supporting accountability. In conclusion, arbitration can be a reliable mechanism for resolving infrastructure disputes if supported by an adequate system.